The Phylosymbiosis Pattern Between the Fig Wasps of the Same Genus and Their Associated Microbiota - Li, Jiaxing; Wei, Xianqin; Huang, Dawei; Xiao, Jinhua (Frontiers in Microbiology, 2022)
Microbial communities are critical for most metazoans. A pattern that phylogenetically related taxa share similar microbial communities is referred to as phylosymbiosis. Most of the previous studies on phylosymbiosis were conducted across the host families or genera. However, it is unclear whether the phylosymbiosis signal are still prevalent at lower taxonomic levels. In this study, 54 individuals from six species of the fig wasp genus Ceratosolen (Hymenoptera: Agaonidae) collected from nine natural populations and their associated microbes were investigated. The fig wasp species were morphologically identified and further determined by mitochondrial CO1 gene fragments, and the V4 region of 16S rRNA gene was sequenced to analyze the bacterial communities. The results declared a significant positive correlation between host genetic characteristics and microbial diversity characteristics, indicating the phylosimbiosis signal between host phylogeny and the related microbiota in the lower classification level within a genus. Moreover, we found that the endosymbiotic Wolbachia carried by fig wasps led to a decrease in bacterial diversity of host-associated microbial communities. This study contributes to our understanding of the role of host phylogeny, as well as the role of endosymbionts in shaping the host-associated microbial community.